Loss of caudal autotomy during ontogeny of Balkan green lizard, Lacerta trilineata - Pafilis, Panayiotis; Valakos, Efstratios D. (Journal of Natural HistoryJournal of Natural History, 2008)
Tail loss is an effective antipredator strategy in many lizards. After loss the tail continues to thrash vigorously and may distract predators away from the escaping lizard. However, autotomy imposes energetic and survival costs (loss of lipid reserves, reduction of reproductive output, impairment of locomotor performance). Autotomy may have been lost when costs exceed benefits, while a substantial reduction or full loss may occur during ontogeny. The Balkan green lizard, Lacerta trilineata is a skilful sprinter despite its robust structure. Predation was simulated in a total of 83 individuals (48 juveniles and 35 adults). All juveniles shed their tail readily while none of the adults autotomized their tails. Postautotomyduration of movement and levels of involving metabolites in shed tails were measured. No differences were found on comparison to other Greek lacertids. These findings suggest that autotomic ability is lost ontogenetically in L. trilineata while post-autotomy energetics seems to be a conservative character.
Keywords: Lacertids; ontogeny; post-autotomy energetics; tail loss